2015
DOI: 10.1016/j.mcn.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Differing phagocytic capacities of accessory and main olfactory ensheathing cells and the implication for olfactory glia transplantation therapies

Abstract: The rodent olfactory systems comprise the main olfactory system for the detection of odours and the accessory olfactory system which detects pheromones. In both systems, olfactory axon fascicles are ensheathed by olfactory glia, termed olfactory ensheathing cells (OECs), which are crucial for the growth and maintenance of the olfactory nerve. The growth-promoting and phagocytic characteristics of OECs make them potential candidates for neural repair therapies such as transplantation to repair the injured spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…This cell class originates as the myelinating cell of the olfactory bulb in fetal development. 114 Olfactory ensheathing cells (OECs) have demonstrated an ability to respond to injury by secretion of an extensive array of neurotrophins, 115 and also act as the primary phagocytic cell of the olfactory bulb, 116 clearing debris and bacteria alike. 117 OECs have shown great promise in restoring function and improving histological injury parameters in animal models of spinal cord injury, [118][119][120][121][122] and they remain one of the few cell types to be utilized experimentally in clinical human spinal cord injury.…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%
“…This cell class originates as the myelinating cell of the olfactory bulb in fetal development. 114 Olfactory ensheathing cells (OECs) have demonstrated an ability to respond to injury by secretion of an extensive array of neurotrophins, 115 and also act as the primary phagocytic cell of the olfactory bulb, 116 clearing debris and bacteria alike. 117 OECs have shown great promise in restoring function and improving histological injury parameters in animal models of spinal cord injury, [118][119][120][121][122] and they remain one of the few cell types to be utilized experimentally in clinical human spinal cord injury.…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%
“…Instead, OECs are the primary immune cells of the olfactory nerve, responsible for clearing both the axonal debris resulting from the olfactory nerve turnover and invading microorganisms [4]. Olfactory neuron dendrites extend directly into the nasal cavity and are constantly exposed to microorganisms, and thus, OECs are considered crucial for protecting the CNS from microbial invasion via the olfactory nerve [4,22,23]. OECs are not one uniform population of cells; there are at least five subpopulations with distinct functions and anatomical locations [24].…”
Section: Homeostatic Rolesmentioning
confidence: 99%
“…After experimental peripheral injury to the olfactory epithelium with zinc sulphate or methimazole, OECs also migrate towards the bulb, undergo morphological changes and increase their level of phagocytosis [4,22,43]. One study, however, showed that OECs did not proliferate or migrate after olfactory nerve axotomy, but instead maintained open channels through which new axons could extend [44], suggesting that the behaviour of OECs is adaptable to the type of nerve injury.…”
Section: Response To Injurymentioning
confidence: 99%
See 2 more Smart Citations